Engineering digital light processing ceramic composites for wide-range flexible sensing arrays - Lee, Dongsu; Kim, Dong Hwi; Kim, Hyungyong; Seung, Hong Min; Song, Hyun-Cheol; Kim, Miso (Pergamon Press Ltd., 2024)
Flexible ceramic composites are promising candidates in capacitive pressure sensing applications. However, the fabrication of complex composite structures typically involves costly and time-consuming processes such as lithography or mold utilization. Digital light processing (DLP)-based 3D printing offers a layer-by-layer approach via photopolymerization, facilitating rapid prototyping of various ceramic composite structures in a single-step synthesis process. This study presents the successful implementation of a flexible ceramic composite based on the highly dielectric ceramic BaTiO3 and conductive MWCNT fillers by employing DLP 3D printing to create an hourglass-shaped stress concentration structure, aiming at enhancing flexible capacitive sensing capabilities. Blending commercial flexible resin with 4-acryloyl morpholine monomers yields a photocurable resin formulation with appropriate mechanical flexibility, photocurability, and optimal suspension viscosity suitable for DLP 3D printing. Furthermore, the proposed 3D-printed sensor arrays comprising hourglass-shaped unit cells demonstrate improved linear sensitivity across a broad pressure range owing to efficient stress concentration effects in a symmetric geometry, as corroborated by both finite element methods and experiments. DLP 3D printing, combined with tailored resin formulations and optimized ceramic and conductive filler contents, enables the rapid prototyping of diverse sensor structures with significantly enhanced sensitivity, highlighting the versatility of this approach for a wide range of applications.